Psychoactive Substance Use among Medical and Pharmacy Students, University of Kufa 2019 - Karrar Mohammed Hasan Al-Gburi1 , Ali Mohammed Abd Alridha1, Roaa Khalid Mohsin Al-Murshedi2 , Abulf (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Medical and pharmacy students are at greater risk of using psychoactive substances. Iraqi medical and health science students are at great danger of using these psychoactive substances and this may be attributed to different reasons, e.g. stressful life. Objectives: Hence, this study was designed to identify the pattern and to investigate the triggering factors associated with psychoactive substance use among medical and pharmacy students, University of Kufa. Subjects and Method: A descriptive cross-sectional institutional-based study was conducted from the period of March to June 2019 at the University of Kufa, in which students were recruited in multistage fashion. Randomly selected students were asked to fill in an online questionnaire prepared based on different standard questionnaires and previous studies. Pearson’s chi-square test (X2) and Fisher-Exact test were used to find the association between categorical variables. A p-value of ? 0.05 was considered significant. Results: Overall, 129 students participated in this study. The mean age of the students was (21.89 ± 2.76). Overall, seven percent of the participants have confessed that they are tobacco smokers. In terms of waterpipe tobacco smoking, 10 out of 129 (7.8%) of the students were hookah smoker and only 2 students (1.6 %) were e-cigarette smokers. Most of the students stated that multiple reasons behind their tobacco smoking. Nearly one-third of participants had quarrels or arguments. While no one had trouble with the police or made something who regretted later. In general, most of the students acknowledged that the use of psychoactive substances carries a risk. In terms of the triggering factors, all factors studied in this study were associated insignificantly with tobacco smoking among the target population (p-value > 0.05), except gender, if they have a family member who smokes or friends who drink alcohol and the age at initiation (p-value < 0.05). No pattern of alcohol consumption and prescription drug among the participants have been identified.